Dissolved methane in anaerobic effluent: emission or recovery? - Zhang, Xiaoyuan (2023)
Various anaerobic processes have been explored for the energy-efficient treatment of municipal wastewater. However, dissolved methane in anaerobic effluent appears to be a barrier towards the energy and carbon neutrality of wastewater treatment. Although several dissolved methane recovery methods have been developed, their engineering feasibility and economic viability have not yet been assessed in a holistic manner. In this perspective, we thus intend to offer additional insights into the cost-benefit of dissolved methane recovery against its emission.